2020
DOI: 10.3389/fncel.2020.590500
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Elasticity Exerts Functional Effects on Primary Microglia

Abstract: Microglia-the brain's primary immune cells-exert a tightly regulated cascade of proand anti-inflammatory effects upon brain pathology, either promoting regeneration or neurodegeneration. Therefore, harnessing microglia emerges as a potential therapeutic concept in neurological research. Recent studies suggest that-besides being affected by chemokines and cytokines-various cell entities in the brain relevantly respond to the mechanical properties of their microenvironment. For example, we lately reported consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…When it comes to the effect of stiffness on the morphology of microglia however, the literature shows some contradiction. In a study performed by Blaschke et al, rat primary microglia were shown to a have less round and more polar morphology and express more anti-inflammatory cytokines when cultured on a soft polydimethylsiloxane (PDMS) substrate (Young’s modulus = 0.6 kPa) versus a stiffer one (Young’s modulus = 1.2 MPa) ( Blaschke et al, 2020 ). On the other hand, Dudiki et al showed in their study that when culturing murine primary microglia on fibronectin-coated hyaluronic acid-based hydrogels of 60 and 600 Pa Young’s moduli, the bipolarization of the cells increased by approximately 3 times on the stiffer hydrogel ( Dudiki et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to the effect of stiffness on the morphology of microglia however, the literature shows some contradiction. In a study performed by Blaschke et al, rat primary microglia were shown to a have less round and more polar morphology and express more anti-inflammatory cytokines when cultured on a soft polydimethylsiloxane (PDMS) substrate (Young’s modulus = 0.6 kPa) versus a stiffer one (Young’s modulus = 1.2 MPa) ( Blaschke et al, 2020 ). On the other hand, Dudiki et al showed in their study that when culturing murine primary microglia on fibronectin-coated hyaluronic acid-based hydrogels of 60 and 600 Pa Young’s moduli, the bipolarization of the cells increased by approximately 3 times on the stiffer hydrogel ( Dudiki et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells have the ability to sense the mechanical strength of their surrounding environment. Studies performed on macrophages have shown the various and inconsistent effects of substrate stiffness on the morphology and cytokine expression of these cells ( Sridharan et al, 2019 ; Blaschke et al, 2020 ; Chen et al, 2020 ; Dudiki et al, 2020 ). While some results show the polarization of microglia on softer substrates ( Blaschke et al, 2020 ), others show the opposite ( Dudiki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, changes in matrix stiffness were found to induce a morphological adaptation of microgliocytes. It was reported that soft substrates enhanced microglia polarization and increased their proliferation ( Blaschke et al, 2020 ). Similar to other cell types, microglial cells were observed to migrate towards the stiffer zone of a mechanical gradient ( Bollmann et al, 2015 ).…”
Section: Mechanosensitivity and Mechanosensingmentioning
confidence: 99%
“…For example, during retinal development, microglia migrate through a stiffness gradient, and subsequently change their shape from ramified to bipolar-rod-like, a process which helps establish the vascular architecture of the developing retina [44]. In the context of microglia, soft PDMS-based elastic substrates (which vary between 1 and 0.6 kPa) have been reported to increase in vitro microglial proliferation and anti-inflammatory characteristics [45], whereas stiffer polyacrylamide/poly-D-lysine-based substrates (10-30 kPa) increase microglial pro-inflammatory characteristics [46]. It has therefore been suggested that brain tissue stiffness changes may be associated with the development of neurodegenerative pathologies; additionally, it has been suggested that microglia may act as mechanosensing cells in the pathogenesis of AD, or indeed other neurodegenerative diseases with neuroinflammatory components.…”
Section: Mechanobiology Of the Microglial Microenvironment In The Bra...mentioning
confidence: 99%